Economic Analysis of Water Treatments for Phosphorus Removal in Florida - Daisuke Sano; Alan Hodges; Robert Degner (EDIS, 2005)
Excessive phosphorus loads in urban and agricultural runoff are identified as one of the greatest threats to the natural environment of Central and South Florida. This study compares the cost effectiveness of two different water treatment systems that have demonstrated an enhanced phosphorus removal ability utilizing aquatic plants and biomass: Wetland Stormwater Treatment Areas (STA) and Managed Aquatic Plant Systems (MAPS). Cost effectiveness, expressed as dollars per kilogram (kg) of phosphorus removed, is calculated from the net present value cost for capital, operation and management, including residue management, and benefits from water storage/supply and recreational use, divided by the projected total phosphorus removal over fifty years. MAPS demonstrated the lowest cost at $24 per kg for systems designed to treat waters with 300 ppb (parts per billion) phosphorus to a level of 155ppb. Reservoir-Assisted STA, which treated 540 ppb to 40 ppb phosphorus concentration in Central Florida, had an estimated cost of $77. STAs starting with concentrations ranging from 40 to 180 ppb and facing a target of 10 ppb phosphorus concentration in South Florida had much higher cost estimates, ranging between $268 and $1,346 per kg. This document is FE576, one of a series of the Food and Resource Economics Department, UF/IFAS. Original publication date November 2005. This is an excerpt of “Economic Analysis of Water Treatments for Phosphorus Removal in Florida,” Food and Resource Economics Department, University of Florida, 2004.